STEAM-5E: A new methodological approach to STEAM based on a critical literature review - Ros, Germán; Rodríguez-Laguna, María Teresa; García-Varela, Ana Belén; Megías Martínez, Clara (Journal of Turkish Science Education, 2026)
Educational institutions and organisations around the world recognise the STEM (Science, Technology, Engineering and Mathematics) and STEAM (A for Arts) paradigms as appropriate frameworks for achieving the key competences needed for the 21st century. However, there are ongoing debates within them and different methodologies to address these debates. First, this work aims to analyse these debates and the diversity of methodologies proposed through a narrative review of the literature following a qualitative content analysis methodology. Secondly, a new framework, STEAM-5E, is proposed to address this complexity. Its basic pillars are the 5E methodology, the integration of STEAM disciplines broadly, the development of creativity across its multiple facets, special consideration for equity, and the search for learner motivation through inquiry, manipulative activities, and collaborative work.  Metacognitive and dialogic processes mediate all learning. Collaboration between researchers and teachers is particularly relevant, according to the basic principles of Design-Based Research, to develop classroom materials adapted to their real context. Several tools are included for implementation evaluation and assessment. Finally, a STEAM-5E project designed for upper primary education (9-11 years old) is presented, along with evidence of its validity and effectiveness. This model could serve as a guide for teachers and researchers in creating and evaluating new STEAM projects.
Keywords: STEAM; STEM; 5E; methodology; review